TEACHER STRATEGIES IN DEALING WITH STUDENTS WITH SPECIAL NEEDS IN ELEMENTARY SCHOOL CLASSROOMS - Romadhon; Sinta Aprianti; Sufia Widi Kasetyaningsih; Al-Amin (CV. ADIBA AISHA AMIRA, 2024)
Inclusive education is an approach to learning that provides inclusion to all learners, regardless of their achievements, disabilities or backgrounds, in the same environment. It involves adjusting the curriculum, teaching methods and additional support to ensure that every student has a fair and equal opportunity to receive a quality education. The research method used in this study is literature review. The results show that first, an inclusive classroom environment requires teachers to implement learning approaches that can effectively meet the individual needs of each student. Through an initial evaluation of learners' abilities and needs, teachers can design an adaptive curriculum tailored to their limitations. Secondly, teachers also need to implement student excellence-based learning strategies, such as multisensory, modeling and tiered assignments. The success of these strategies relies heavily on collaboration between teachers, parents, and various experts such as educational psychologists and therapists. Open and continuous communication between all parties is essential to ensure the strategies implemented remain appropriate and effective. Thus, the implementation of appropriate strategies and strong cooperation can provide equal opportunities for learners with disabilities to succeed in their learning.